The Moderating Role of Board Characteristics in the Relationship Between Firm Factors and ESG Performance in Indonesia - Juan Kurnia; Iwan Kusmayadi (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the influence of firm-specific characteristics namely firm size, firm age, profitability (ROA), and leverage (DAR)on Environmental, Social, and Governance (ESG) performance, with the Board Size of Commissioners (BSC) and Board Independence of Commissioners (BIC) as moderating variables. The research employs a quantitative causal approach using secondary data from 78 non-financial companies listed on the Indonesia Stock Exchange during 2019–2023, generating 390 firm-year observations. Data were analyzed using multiple linear regression with the Moderated Regression Analysis (MRA) method through SPSS 26. The results indicate that firm age positively and significantly affects ESG performance, while profitability (ROA) has a significant negative influence. Firm size and leverage show no significant effects. Furthermore, BSC strengthens the relationship between firm size and profitability with ESG, whereas BIC enhances the link between profitability and ESG performance. These findings highlight the critical role of corporate governance mechanisms in aligning financial objectives with sustainability goals, providing valuable insights for companies and policymakers to improve ESG governance practices in Indonesia.